COVID-19 pandemic lockdown-induced altered sleep/wake circadian rhythm, health complaints and stress among traffic police personnel in India. (2nd January 2021) - Dey, Arindam; Majumdar, Piya; Saha, Atanu; Sahu, Subhashis
ABSTRACT: COVID-19 is a highly contagious disease caused by Severe Acute Respiratory Syndrome coronavirus-2, capable of high human transmission. To protect against the COVID-19 pandemic, the World Health Organization proposed intervening guidance that included movement restrictions, isolation, restriction of national and international travel or movement, and full or partial closure of organizations and institutions. Police personnel play a vital role in safeguarding the spread of COVID-19; thus, potentially causing severe stress due to increased consignment and direct exposure to infection during duty. The study aimed to determine the effect of the added stress of the COVID-19 pandemic and population lockdown on the sleep/wake 24 h rhythm of traffic police. A concise online questionnaire survey was conducted among the traffic police personnel of India. Collected data were analyzed statistically. Disorientation of working schedule, fear of being vulnerable to disease, pressure of maintaining law, and orders during lockdown increased stress level. The survey identified discontinuation of sleep, shift of mid-sleep time, increase in depression, plus stress and anxiety among traffic police personnel that affected their chronobiological milieu. Proper awareness of adequate health and safety measures, use of personnel protection equipment, regular conversation with family members, and meditation can help reduce stress during this pandemic situation.